C Programming Absolute Beginner's Guide - Greg Perry; Dean Miller (USA Que, 2015)
Updated for C11 Write powerful C programs..."without "becoming a technical expert! This book is the fastest way to get comfortable with C, one "incredibly "clear and easy step at a time. You'll learn all the basics: how to organize programs, store and display data, work with variables, operators, I/O, pointers, arrays, functions, "and much more. "C programming has neverbeen this simple! Who knew how simple C programming could be? This is today's best beginner's guide to writing C programs-"and to learning skills you can use ""with practically any language. "Its simple, practical instructions will help you start creating useful, reliable C code, from games to mobile apps. Plus, it's fully updated for the new C11 standard and today's free, open source tools! Here's a small sample of what you'll learn: - Discover free C programming tools for Windows, OS X, or Linux- Understand the parts of a C program and how they fit together- Generate output and display it on the screen- Interact with users and respond to their input- Make the most of variables by using assignments and expressions- Control programs by testing data and using logical operators- Save time and effort by using loops and other techniques- Build powerful data-entry routines with simple built-in functions- Manipulate text with strings- Store information, so it's easy to access and use- Manage your data with arrays, pointers, and data structures- Use functions to make programs easier to write and maintain- Let C handle all your program's math for you- Handle your computer's memory as efficiently as possible- Make programs more powerful with preprocessing directives.
Keywords: Programming; Nonfiction; Technology; Technical; Computers; (ICE-1111) Imperative Programming